Renewable Energy Consumption, Education and Economic Growth in Brazil, Russia, India, China, South Africa - Tsaurai, Kunofiwa; Ngcobo, Lindiwe (International Journal of Energy Economics and Policy, 2020)
The study investigated two aspects, namely, (1) the impact of renewable energy consumption on economic growth in BRICS (Brazil, Russia, India, China, South Africa) and (2) whether education is a channel through which renewable energy consumption affects economic growth in BRICS. Panel data analysis such as fully modified ordinary least squares (FMOLS), pooled ordinary least squares (POLS) and fixed effects methods were used with data ranging from 1994 to 2015. Both models across all the three estimation techniques show that renewable energy consumption had a significant negative effect on economic growth in support of the findings by Silva et al (2012) and Lee and Jung (2018). What is also clear across all the three panel data analysis methods used is that education reduced the size of the negative effect of renewable energy consumption on economic growth in BRICS. In other words, education is a channel through which renewable energy consumption's influence on economic growth is enhanced, in support of views by Dunn and Mutti (2004), Ozcicek and Agpak (2017) and Lawrence et al. (1991). The implication of the study is that BRICS countries are therefore urged to invest more in education as that is more likely to enhance the impact of renewable energy consumption on economic growth. Keywords: Renewable Energy Consumption; Education; Growth; BRICS; Panel Data JEL Classifications: Q2, I2, F43, P2 DOI: https://doi.org/10.32479/ijeep.8497